Strategi Gerakan Sosial Transnasional dalam Menentang “Rape Culture” (Studi Kasus: Transnasionalisasi SlutWalk Movement di Kanada, Amerika Serikat, Australia, dan Inggris) - Sari, Ni Komang Wisvani Manika; Wiranata, I Made Anom; Suwecawangsa, Adi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 1 (2024): JURNAL DIKSHI, 2024)
The aim of this research is to understand the strategies used by SlutWalk activist network in transnationalizing the movement using qualitative methods that analyze phenomena with theory. The SlutWalk movement has successfully transnationalized to various countries relatively quickly by taking counter–hegemonic actions against the hegemony of sexuality as a precondition for the movement to oppose “rape culture”. Thus, this research reveals that the activist network employed strategies to mobilize resources, take advantage of political opportunity structures, frame the movement to engage public support, and build solidarity through collective identity, resulting in the transnationalization of the movement. Despite lacking a single leadership structure, the formation of a transnational advocacy network also highlights the SlutWalk movement as a global concern. Keywords : Hegemony of Sexuality, Rape Culture, SlutWalk, Strategy of Social Movement, Transnational Advocacy Network